The degree of employing linguistic intelligence strategies in education from the perspective of first-cycle basic education teachers (Journal of Hama University, 2026)
The aim of the research was to identify the degree of employment of the linguistic intelligence strategy by first-cycle teachers. The research sample consisted of 334 male and female first-cycle teachers who were randomly selected from schools in Hama city. The researcher used the descriptive approach. To achieve the research objectives, the researcher designed a questionnaire consisting of 14 items. The apparent validity of the tool was confirmed by presenting it to the arbitrators. Reliability was also confirmed by applying the tool to a survey sample, and calculating the reliability coefficient, which reached 0.841. The research results showed that the level of employment of the linguistic intelligence strategy by first-cycle teachers was high, in addition to differences among first-cycle teachers in employing this strategy according to the qualification variable in favor of the diploma. It also showed differences among first-cycle teachers in employing the linguistic intelligence strategy according to the variable of their attendance at courses The validity of teachers who underwent courses. The researcher made several proposals based on these results: 1. Conduct comparative studies between the use of linguistic intelligence at different educational levels, or between different geographical areas, to measure variance and analyze its causes. 2. Study the relationship between linguistic intelligence and students' academic achievement, and the extent of the teacher's contribution to its development according to well-studied strategies
Keywords: Keywords: Linguistic Intelligence Strategy